Analysis of Opportunities and Challenges of Using Fintech in Islamic Banking in the Digital Era - Nayla Fibri Anjani; Eky Okta Triana; Ika Yuli Astuti; Kaka Raflika Renandar; Widia Alfa Rifa; Ade Mayang Sari (Journal of Economics and Business, 2025)
The rapid growth of digital technology has driven innovation in Islamic banking, with fintech playing a key role in improving efficiency, expanding financial access, and strengthening competitiveness. This literature-based study analyzes the opportunities and challenges of fintech adoption in Islamic banking. Findings indicate that fintech creates opportunities through improved service effectiveness, broader market reach, enhanced service quality, easier transactions, and strong regulatory support. However, several challenges remain, including cybercrime risks, uneven digital infrastructure, low fintech literacy among the public, and strict Sharia compliance requirements. Overall, fintech has great potential to support the development of Islamic finance if supported by the right digital strategies, stronger regulations, and increased user literacy, providing valuable insights for industry players, regulators, and academics in building an inclusive and sustainable Islamic fintech ecosystem.